Chemistry for environmental engineering - Sawyer, Clair N.; McCarry, Perry L.; Parkin, Gene F. (New York : McGraw Hill Education, 1994)
This edition features a substantial revision of the organic chemistry sections; additions include coverage of radiochemistry and statistical analysis. Example problems, some with solutions, allow students to test their progress and check their results immediately.
Contents: Fundamentals of chemistry for environmental engineering Water and wastewater analysis
Includes bibliographical references.
Keywords: ENVIRONMENTAL CHEMISTRY